Western Lands, Western Voices : Essays on Public History in the American West - Thompson, Gregory C. (Gregory Coyne), 1943-; Smoak, Gregory E., 1962- (Book collections on Project MUSE., 2021)
"This collection of essays explores the meanings and uses of contemporary public history in the American West"--